Spilne bases in digital data compression problems - Білецький, А. Я.; Шелевицький, I. B.; Шутко, B. M.; Ткаченко, Є. В. (Proceedings of National Aviation University (archive), 2000)
It is proposed to use spline bases coordinated with amplitude spectrum data in the approximation data problems in order to compress them. The efficiency of such approach is demonstrated by examples of approximation data of bases with different spectrum properties